2016
DOI: 10.1111/1751-2980.12406
|View full text |Cite
|
Sign up to set email alerts
|

Alginate antacid (Gaviscon DA) chewable tablets reduce esophageal acid exposure in Chinese patients with gastroesophageal reflux disease and heartburn symptoms

Abstract: DA alginate antacid was statistically significantly superior to placebo in reducing post-prandial acid exposure without serious clinically relevant health risks. These findings suggest DA alginate antacid tablets are appropriate for treating acid reflux in Chinese GERD patients with heartburn symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…diabetic foot ulcers (DFUs) due to their biocompatible, adhesive, antibacterial and hemostatic properties. 112,114,116,117 The purpose of the study proposed by Akiyode and Boateng 112 was to investigate two bioactive polysaccharide polymers kappa-carrageenan (CARR) and sodium alginate (SA) incorporated with microbial biosurfactants (BSs) as medicated wafer dressings for potential application in chronic wounds. Wafers were loaded with BSs at concentrations of 0.1% and 0.2% rhamnolipids (RL) and 0.1% and 5% sophorolipids (SL).…”
Section: Mucoadhesive Drug Delivery Systemsmentioning
confidence: 99%
“…diabetic foot ulcers (DFUs) due to their biocompatible, adhesive, antibacterial and hemostatic properties. 112,114,116,117 The purpose of the study proposed by Akiyode and Boateng 112 was to investigate two bioactive polysaccharide polymers kappa-carrageenan (CARR) and sodium alginate (SA) incorporated with microbial biosurfactants (BSs) as medicated wafer dressings for potential application in chronic wounds. Wafers were loaded with BSs at concentrations of 0.1% and 0.2% rhamnolipids (RL) and 0.1% and 5% sophorolipids (SL).…”
Section: Mucoadhesive Drug Delivery Systemsmentioning
confidence: 99%
“…Data from all the patients were accumulated, and the results showed significant benefits of GDA statistically. It was concluded that GDA is safe and effective for the treatment of GORD …”
Section: Resultsmentioning
confidence: 99%
“…Several studies also proved that alginate could decrease acid exposure in the postprandial period. [235][236][237] Alginate showed a better clinical effect in reducing reflux-related symptoms than placebo or non-alginate antiacid. 238,239 In a meta-analysis, alginate-antacid also showed 60.0% relative benefit compared to placebo.…”
Section: Alginate-based Therapymentioning
confidence: 99%